Cytidine and dCMP Deaminases-Current Methods of Activity Analysis - Ligasová, Anna; Horejšová, Martina; Brumarová, Radana; Friedecký, David; Koberna, Karel (International journal of molecular sciences, 2025)
Cytidine deaminase (CDA) and deoxycytidine monophosphate deaminase (DCTD) play crucial roles in pyrimidine metabolism, affecting DNA synthesis, cell cycle progression, and the efficacy of numerous nucleoside analog-based chemotherapeutics. Given their significance, accurate and sensitive measurement of their enzymatic activity is paramount for both fundamental biochemical research and clinical applications. This review provides a comprehensive overview of the methodologies used to assess CDA and DCTD activity, both established and emerging. We systematically categorize and discuss various approaches, including spectrophotometric, fluorimetric, liquid chromatography-based (Ultraviolet-Visible, fluorescence, and mass spectrometry), radiometric, and cell-based assays. For each method, we present its underlying principles, advantages, and limitations. Furthermore, we draw comparisons across the techniques to highlight their suitability for specific research questions.
Keywords: spectrophotometry; Cytidine; cytidine deaminase; Chromatography, Liquid; cytidindeaminasa; Enzyme Assays; modified nucleosides; LC-MS; Cytidine Deaminase; dCMP deaminase; Mass Spectrometry; chromatografie kapalinová; cytidin; cell-based approaches; Animals; lidé; Humans; zvířata; hmotnostní spektrometrie; enzymatické testy